2011
DOI: 10.1002/mabi.201100295
|View full text |Cite
|
Sign up to set email alerts
|

Natively Unfolded State for Engineering Nanoscale Fibrillar Arrays

Abstract: A generic rationale for the fabrication of high aspect ratio fibrillar nanoscale arrays is described. The design emulates an intermittence effect observed for β-structured α-synunclein fibrils, reported herein, in a structurally unrelated α-helical fiber. The generated nanoarrays are composed of periodic nanosized segments separated at uniform distances of unfolded regions. These regions can be targeted for conformational binding and refolding with metal nanoparticle-peptide conjugates for the conversion of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…7 the nanoparticles are almost exclusively organized at the surface of the peptide fiber bundles. A similar effect was reported by Cherny and coworkers [41]. Since the nanoparticle concentration was 0.05 µM, an excess of peptide was present in solution.…”
Section: Resultssupporting
confidence: 81%
“…7 the nanoparticles are almost exclusively organized at the surface of the peptide fiber bundles. A similar effect was reported by Cherny and coworkers [41]. Since the nanoparticle concentration was 0.05 µM, an excess of peptide was present in solution.…”
Section: Resultssupporting
confidence: 81%
“…The polymeric micro‐ or nanoparticles, that may or may not contain drugs, are functionalized with oppositely charged β‐sheet peptides to direct particle assembly. Peptide directed assembly of nanoparticles has received some attention, but so far it has been limited to inorganic nanoparticle arrays using self‐assembled peptide structures as templates . For example, Nikhil et al reported a well‐organized one‐dimensional gold nanoparticle line formed on self‐assembled polypeptide template, and the formation of the nanoparticle array was directed by regulatory‐presented positive charges on peptide fiber surface .…”
Section: Introductionmentioning
confidence: 99%
“…Peptide directed assembly of nanoparticles has received some attention, but so far it has been limited to inorganic nanoparticle arrays using self-assembled peptide structures as templates. [23][24][25] For example, Nikhil et al reported a well-organized one-dimensional gold nanoparticle line formed on self-assembled polypeptide template, and the formation of the nanoparticle array was directed by regulatory-presented positive charges on peptide fiber surface. [24] Another recent report showed a simple method to fabricate a two-dimensional gold nanoparticle line pattern on mica surface from a designer b-sheet peptide (LELC16)-functionalized gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Using peptide directed assembly of nanoparticles has received limited attention, and prior to this work was limited to inorganic nanoparticles (i.e. gold nanoparticles, nanotubes) arraysusing self-assembled peptide structures as templates or as assembly ligands (55)(56)(57)(58). For example, Nikhil et al (56) reported a well-organized one-dimensional gold nanoparticle line formed on a self-assembled polypeptide template, and the formation of the nanoparticle array was directed by positive charges on peptide fiber surface.…”
Section: Self-assembled Peptide-nanoparticle Precedentsmentioning
confidence: 99%